Chondrodysplasia Bulldog type in cattle in the state of Bahia, Brazil - D’Soares, Charmila S.; Muramoto, Caterina; Silva, Antonio W. O.; Freitas, Moisés D.; Carvalho, Vitor S.; Souza, Ana Caroline S. N.; Mendonça, Mucio F. F.; Biscarde, Carmo E. A.; Leal, Paula V.; Peixoto, Tiago C. (Brazilian Journal of Veterinary Pathology, 2020)
Chondrodysplasia is a congenital or hereditary disorder of the endochondral ossification that results in several degrees of disproportionate dwarfism. Reports of this disease are scarce in the national literature and do not emphasize radiographic characteristics. The goal of this study was to describe the clinicopathological and radiographic aspects of a case of Bulldog type chondrodysplasia in a crossbred bovine fetus in the state of Bahia, Brazil. The fetus exhibited a rounded and disproportionate skull, bilateral exophthalmos, inferior brachygnathism, partial tongue protrusion, extremely short limbs, short vertebral column and ventral abdominal hernia. Radiographic evaluation revealed that the diaphysis were the only calcified bone portions of the limbs, that the vertebral column was shortened without vertebral spinal processes and that there was craniofacial disproportion. Microscopic of the femur showed an irregular epiphyseal plaque, formed by dense clusters of chondrocytes with absence of growth plate zones. The metaphysis was markedly short and consisted of thick bony trabeculae, surrounded by cartilaginous islands. It was concluded that fetuses with Bulldog type chondrodysplasia exhibit slight morphological and radiographic variation according to the affected breed and that the gene carrier of chondrodysplasia is present in the miniature Jersey and Punganur population in the state of Bahia.